2014
DOI: 10.1021/ol501372u
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Enantioselective Addition of Organoaluminum Reagents to N-Tosyl Ketimines

Abstract: Rhodium(I)/Binap complexes catalyze highly enantioselective additions of methyl- and arylaluminum reagents to cyclic α,β-unsaturated N-tosyl ketimines. Depending on the solvent and substituents at the ring, the reaction occurs either in a 1,2-manner to deliver α-tertiary allylic amines or in a 1,4-manner to yield, after subsequent reduction, 3-substituted cycloalkyl amines. Well known in the case of the respective cycloalkenones, these first transformations of the aza-analogues enable the synthesis of amine st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…351 In the conversions of ketimine 416, it was observed that the facial selectivity was the same for the addition of both methyl and phenyl groups, which is an indication of similar catalytic cycles. Nevertheless, the facial selectivities of the 1,4-addition are inverted, while the selectivity of the latter is related to that of a standard proposed by Hayashi-Miyaura for the reaction with arylboronic acids and Binap as a chiral ligand.…”
Section: Organoaluminiumsmentioning
confidence: 90%
See 2 more Smart Citations
“…351 In the conversions of ketimine 416, it was observed that the facial selectivity was the same for the addition of both methyl and phenyl groups, which is an indication of similar catalytic cycles. Nevertheless, the facial selectivities of the 1,4-addition are inverted, while the selectivity of the latter is related to that of a standard proposed by Hayashi-Miyaura for the reaction with arylboronic acids and Binap as a chiral ligand.…”
Section: Organoaluminiumsmentioning
confidence: 90%
“…This reaction route could apply to Rh-catalyzed 1,4-additions of a wide range of organometallic reagents. 350,351 Alkenylrhodium 392 can subsequently be added to a,b-enones 1 to afford oxa-p-allyl-Rh 393, followed by reaction with alkenylzirconocene chloride 389 to provide alkenylrhodium intermediate 392 and afford zirconium enolate 394 (Scheme 194). 349 In 2004, Hanzawa et al reported on a highly efficient conjugate addition reactions of alkenyl zirconocene chloride complexes 395 to a,b-enones, a,b-enoic acid esters, and a,b-enoic acid amides 396, 397, 398 catalyzed by [RhCl(cod)] 2 catalyst to provide 1,4-adducts 399, 400, 401 in excellent yields.…”
Section: Organozirconiumsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advances in this area have been achieved in the field of Rh- and Pd-catalysed addition of Csp 2 -nucleophiles to N -sulfonyl ketimines using boron reagents567. However, the addition of Csp 3 -nucleophiles is restricted to methylations and ethylations of a small set of ketimines using organozinc or organoaluminium reagents with Cu, Zr or Rh catalysts8910.…”
mentioning
confidence: 99%
“…von Zezschwitz et al utilized α,β-unsaturated C=N exocyclic ketimines 73 in catalytic asymmetric methylation and phenylation with organoaluminum reagents 74 (Scheme 16). 46 The reaction generally proceeded with a Rh/ BINAP complex in a 1,2-fashion in diethyl ether, whereas the reaction in toluene predominantly afforded the 1,4-adduct.…”
mentioning
confidence: 99%